Facile expeditious one-pot synthesis and antifungal evaluation of disubstituted 1, 2, 3-triazole with two amide linkages. Issue 23 (2nd December 2017) - Kaushik, C. P.; Luxmi, Raj
ABSTRACT: A library of twenty five amide linked 1, 4-disubstituted 1, 2, 3-triazoles have been prepared through a facile expeditious synthetic protocol involving Cu(I) mediated cyclization of N -(2-methylbut-3-yn-2-yl)aromatic amides and in situ generated 2-azido- N -substituted propanamides. Structures of newly synthesized compounds (5a –5y ) were confirmed by analytical techniques, such as FTIR, 1 H NMR, 13 C NMR, and HRMS. In vitro antifungal activity was also examined against two fungal strains Candida albicans and Aspergillus niger by serial dilution method. The compounds5 m and5w exhibited appreciable potent activity. GRAPHICAL ABSTRACT: